UJI BIOAKTIVITAS GETAH IPU (Antiaris toxicaria, Lesch.) SEBAGAI INSEKTISIDA NABATI The Bioactivity Test of Sap Ipu (Antiaris toxicaria, Lesch.) as Vegetative Insecticide: Ahmad Mujaffar1* , Zainal Abidin 2 , Kissinger 2 , Badaruddin 2 dan Muhammad Damiri 1 - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTThe aim of this research is to analyze the potential diversify utilization of the sap of A.toxicaria as naturalinsecticide. This based on Lethal Dosis 50 (LD50) with testing and analyzed by results of toxicity test of 5 (five)fractions from the isolation sap of A.toxicaria make use of ticks rice (Calandra oryzae) as bioindicator. Dose ofthe presentation applied is: 500 ppm, 1000 ppm, 1500 ppm, 2000 ppm and 2500 ppm, plus one units of thetreatment, namely control it solvent. Each level dose of done with 3 (three) time tests. The results of this researchshown the effect of toxic fractions ethanol with a dose of 2221,26 ppm long the exposure of 5 days have causedthe death 50% rice ticks. Based on the result can be concluded that the extract fraction ethanol have theeffectiveness of and potential as insecticide with LD50, 5 days with the amount of 2221,26 ppm.Keywords: A.toxicaria, Calandra oryzae, sap, natural insecticide, lethal dosis.